Solidariedade: bases e manifestações em organizações não convencionais – o caso curto café - Costa, Cesar Renato Ferreira da (2016)
Solidarity is a fundamental element of associated human experience, being investigated in several areas of knowledge. Studies converge when it comes to understand it as an unifying element of social organization. In Organizational Studies there is convergence in the characterization of solidarity as the substance or group of elements, constituted historically, that guarantee solidity to a particular organizational reality. In its modern design, investigated in Applied Social Sciences, the solidarity bases only refer to bureaucratic organizations, guided by the capitalist mode of production convention. However, resistance enclaves point to organizational experiences historically not aligned to the conventions imposed by the modernist organizational design, whose foundations of solidarity are supposedly different. This thesis is focused on the investigation of the bases and demonstrations of solidarity in the context of non-conventional organizational experiences to the capitalist mode of production. The empirical research was based on an exploratory study with a qualitative approach, designed as a case study in depth and driven by participant observation, in Rio cafeteria Curto Café, suggested a priori as non-conventional. The data collection method was driven by observation and recording events, images, artifacts, activities and narratives, and these last produced by semi-structured interviews and testimonials in oral history, in ninety days of observatory participation in the organization, between the months of January to October 2015. The data analysis was performed from a triangulation that related empirical data with theoretical references, from an epistemological critical lens. In the empirical research, the study systematized the information considering the manifestations of organizational solidarity observed in Curto Café and, based on them, identified the solidarity bases that kept the organization. The suggested triangulation, based on the definitions of conventional organizations and nonconventional organizations, the foundation of the first recognized as (a) accumulation of capital, (b) technical efficiency, and (c) market orientation were confronted critically one by one, with the bases found in Curto Café, being respectively (a) sufficiency, (b) conviviality, and (c) communitarian orientation. As a result the thesis recognized Curto Café as a nonconventional organization, the presentation of the bases and manifestations of organizational solidarity that keeps being distinct from the bases proposed for conventional organizations driven by the dominant paradigm of the capitalist system.